Internalizing Character Values and Strengthening Social Bonds through Peresean: An Ethnopedagogical Study of the Sasak Community - Ade Juraedah; Sri Rejeki; Aliahardi Winata; Noel Jimbai Balang (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
The Peresean tradition is a distinctive cultural heritage of the Sasak people, combining elements of traditional martial arts, local wisdom, sportsmanship and character education into a single cultural practice passed down from generation to generation. It is important to study this tradition, given that its survival faces various challenges due to modernisation and a decline in the younger generation’s interest in local culture. In addition to serving as a cultural performance, Peresean also acts as a medium for passing on the values of courage, self-control, respect, solidarity, and social responsibility through the direct involvement of the community. This study is to examine the Peresean tradition of the indigenous Sasak community as a means of internalizing character values through an ethnopedagogical perspective, as well as to explore its contribution to strengthening social bonds within the Sasak community. This study uses qualitative methods. Data collection was conducted through observation and in-depth interviews with pepadu, pekembar, traditional leaders, academics, and the community, as well as field documentation in Bonjeruk Village, Central Lombok Regency. Data analysis was conducted using Miles and Huberman's method with the stages of data collection, data reduction, data presentation, and conclusion drawing/verification. This study draws on Berger and Luckmnn’s Social Construction Theory, which explains that cultural values are formed and internalized through the process of social interaction. The results of the study show that the Peresean tradition not only functions as a cultural performance but also as a medium of education based on local culture that instills social and moral values through role modeling, habituation, and community involvement. Peresean plays an important role in strengthening social solidarity and the collective identity of the Sasak community. This study makes a theoretical contribution by broadening our understanding of the role of local cultural traditions as a means of internalizing character values in community life. In practical terms, the findings of this study can be used as a basis for developing education grounded in local wisdom to strengthen students’ character and support sustainable efforts to preserve local culture.